Compact and Wideband Parallel-Strip 180° Hybrid Coupler with Arbitrary Power Division Ratios. (26th December 2013) - Chiu, Leung; Xue, Quan
Abstract : This paper presents a class of wideband 180° hybrid (rat race) couplers implemented by parallel-strip line. By replacing the 270° arm of a conventional 180° hybrid coupler by a 90° arm with phase inverter, the bandwidth of the coupler is greatly enhanced and the total circuit size is reduced by almost half. Simple design formulas relating the characteristic impedance of the arms and power division ration are derived. To demonstrate the concept, four couplers with different power division ratios of 1, 2, 4, and 8 were designed, fabricated, and tested. S -parameters of the coupler are simulated and measured with good agreement. All working prototypes operate more than 112% impedance bandwidth with more than 25 dB port-to-port isolation and less than 5° absolute phase imbalance. The proposed 180° hybrid couplers can be employed as a wideband in-phase/differential power divider/combiner, which are essential for many RF and microwave subsystem designs.